Perumusan Visi dan Misi Jasa Pendidikan, Perencanaan Pemasaran, Serta Pemasaran Strategis Jasa Pendidikan - Supian, Sopwan; Mu'in, Abdul; Zohriah, Anis (Universitas Pahlawan Tuanku Tambusai, 2024)
Every educational institution must have a vision and mission, and must plan and market its educational services to achieve the desired goals. Vision and mission are the most important parts used in activities to describe achievements in achieving the desired conditions for all stakeholders to achieve educational goals. The aim of this research is to describe and analyze how vision and mission can be developed in formal educational institutions. This research is based on literature research from relevant books and academic journals. The overall conclusion from the analysis of this literature review study is that the preparation of a vision and mission requires in-depth research and it is important to involve various stakeholders to achieve the desired overall goals. Even though the vision and mission of a school contains something very important that gives appropriate weight to all aspects in realizing the school's identity, this is already covered in reading the existing vision and mission. Supervision is necessary if there are gaps in the actual order. explanation of vision and mission (but in this case all stakeholders.